2010
DOI: 10.1056/nejmoa0912611
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Tai Chi for Fibromyalgia

Abstract: Background Previous research has suggested that tai chi offers a therapeutic benefit in patients with fibromyalgia. Methods We conducted a single-blind, randomized trial of classic Yang-style tai chi as compared with a control intervention consisting of wellness education and stretching for the treatment of fibromyalgia (defined by American College of Rheumatology 1990 criteria). Sessions lasted 60 minutes each and took place twice a week for 12 weeks for each of the study groups. The primary end point was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
266
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(280 citation statements)
references
References 40 publications
9
266
0
5
Order By: Relevance
“…While the prevalence of neck and low-back pain were comparable between the 2 generations, the baby boomers were more likely to report head and facial pain. Several nonpharmacological interventions, such as acupuncture, 33 tai chi, 34 yoga, 35 and massage, 36 have shown evidence in managing chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…While the prevalence of neck and low-back pain were comparable between the 2 generations, the baby boomers were more likely to report head and facial pain. Several nonpharmacological interventions, such as acupuncture, 33 tai chi, 34 yoga, 35 and massage, 36 have shown evidence in managing chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these treatments cannot be recommended for the management of FM. In contrast, recent research testing mind-body and meditative movement interventions has found considerable benefits, especially for tai chi, in patients with FM 17,18 . Further useful treatments are hydrotherapy and thermal therapy 19 .…”
Section: Fibromyalgiamentioning
confidence: 90%
“…29 Limitations of these studies include small sample sizes, large dropout rates, and absence of a double-blind study design. 25,26,28 In all the studies reviewed, there were no adverse effects from the use of a tai chi exercise program (Table 3). Similar studies show the benefits of yoga for pain relief.…”
Section: Mind-body and Energy Therapiesmentioning
confidence: 98%
“…9 Most tai chi studies have focused on its use in musculoskeletal pain, specifically osteoarthritis [25][26][27] and fibromyalgia. 28 In addition, tai chi has been studied for its use in fall prevention and as an adjunct for rehabilitation in patients with heart failure. 29 Limitations of these studies include small sample sizes, large dropout rates, and absence of a double-blind study design.…”
Section: Mind-body and Energy Therapiesmentioning
confidence: 99%